Life cycle, financial frictions and informal labor markets: The case of Chile - Damian Pierri; Enrique Kawamura (Journal of Applied Economics, 2022)
We study the implications of economic policies on household's decisions. We focus on Chile in 2019. Using a life-cycle search model and survey data, we found that an equivalent change in labor tax rates and non-contributory pensions (NCP) have opposite effects on labor markets, specifically on informality and unemployment duration. NCP offers a milder trade-off as it produces a second-order increase in informality. However, due to the presence of informal labor markets and financial frictions, non-retired agents increase their current consumption only after a tax cut. That is, a positive wealth shock can reduce consumption. When we consider the impact on welfare, as households are assumed to value only consumption, cutting taxes seems to be preferred. We characterize labor market and consumption-savings decisions. We found two effects operating in opposite directions: substitution and wealth. The latter prevails suggesting that the life cycle aspects of the labor market are critical.
Keywords: 330; life-cycle; Search models; simulation-based estimation; social-security reform